Re-evaluation of the taxonomy of the Mitis group of the genus Streptococcus based on whole genome phylogenetic analyses, and proposed reclassification of Streptococcus dentisani as Streptococcus oralis subsp. dentisani comb. nov., Streptococcus tigurinus as Streptococcus oralis subsp. tigurinus comb. nov., and Streptococcus oligofermentans as a later synonym of Streptococcus cristatus - Jensen, Anders; Scholz, Christian F. P.; Kilian, Mogens (International journal of systematic and evolutionary microbiology, 2016)
The Mitis group of the genus Streptococcus currently comprises 20 species with validly published names, including the pathogen S. pneumoniae. They have been the subject of much taxonomic confusion, due to phenotypic overlap and genetic heterogeneity, which has hampered a full appreciation of their clinical significance. The purpose of this study was to critically re-examine the taxonomy of the Mitis group using 195 publicly available genomes, including designated type strains for phylogenetic analyses based on core genomes, multilocus sequences and 16S rRNA gene sequences, combined with estimates of average nucleotide identity (ANI) and in silico and in vitro analyses of specific phenotypic characteristics. Our core genomic phylogenetic analyses revealed distinct clades that, to some extent, and from the clustering of type strains represent known species. However, many of the genomes have been incorrectly identified adding to the current confusion. Furthermore, our data show that 16S rRNA gene sequences and ANI are unsuitable for identifying and circumscribing new species of the Mitis group of the genus Streptococci. Based on the clustering patterns resulting from core genome phylogenetic analysis, we conclude that S. oligofermentans is a later synonym of S. cristatus. The recently described strains of the species Streptococcus dentisani includes one previously referred to as 'S. mitis biovar 2'. Together with S. oralis, S. dentisani and S. tigurinus form subclusters within a coherent phylogenetic clade. We propose that the species S. oralis consists of three subspecies: S. oralis subsp. oralis subsp. nov., S. oralis subsp. tigurinus comb. nov., and S. oralis subsp. dentisani comb. nov.